RETRACTED: Sustainable human resource management: A transformation perspective of human resource management functions through optimised artificial intelligence - Adz Zikri, Arif Furqon Nugraha; Widianto, Sunu; Komaladewi, Rita (BISMA (Bisnis dan Manajemen), 2024)
We would like to formally announce the retraction of the article “Sustainable Human Resource Management: A Transformation Perspective of Human Resource Management Functions Through Optimized Artificial Intelligence,” published in Volume 16, Issue 2, May 2024. This retraction arises from the discovery that the article was also published in the Jurnal Aplikasi Bisnis dan Manajemen, violating our policy regarding duplicate publication. As a result, the document associated with this article, including its content and any supplementary materials, has been retracted from the journal BISMA (Bisnis dan Manajemen). It is, therefore, essential to take appropriate steps to eliminate all references to this article.